2011
DOI: 10.1007/s00066-011-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin superior to carboplatin in adjuvant radiochemotherapy for locally advanced cancers of the oropharynx and oral cavity

Abstract: For adjuvant radiochemotherapy of patients with locally advanced cancer of the oropharynx and oral cavity, cisplatin appears preferable to carboplatin as it resulted in better outcomes without increased toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 16 publications
1
32
1
2
Order By: Relevance
“…Moreover, a randomised non-inferiority trial comparing the use of single agent carboplatin against cisplatin as a radiosensitiser had successfully demonstrated similar survival outcomes [91]; with the reported 3 year OS was 79.2% and 77.7% respectively (p=0.9884, HR 0.83 95% CI 0.613-1.010) [91]. A more recent retrospective study demonstrated significant superiority of cisplatin to carboplatin in terms of adjuvant chemoradiotherapy for locally advanced oropharynx and oral cavity with a 3 year local control rate of 85% versus 62%, 3 year OS of 78% versus 51% and favourable toxicity profile [92] For metastatic/recurrent head and neck cancers, 5-fluorouracil (5-FU) and platinum doublets are well-established standards of care. With respect to comparative studies, Forastiere et al…”
Section: Head and Neck Cancersmentioning
confidence: 56%
“…Moreover, a randomised non-inferiority trial comparing the use of single agent carboplatin against cisplatin as a radiosensitiser had successfully demonstrated similar survival outcomes [91]; with the reported 3 year OS was 79.2% and 77.7% respectively (p=0.9884, HR 0.83 95% CI 0.613-1.010) [91]. A more recent retrospective study demonstrated significant superiority of cisplatin to carboplatin in terms of adjuvant chemoradiotherapy for locally advanced oropharynx and oral cavity with a 3 year local control rate of 85% versus 62%, 3 year OS of 78% versus 51% and favourable toxicity profile [92] For metastatic/recurrent head and neck cancers, 5-fluorouracil (5-FU) and platinum doublets are well-established standards of care. With respect to comparative studies, Forastiere et al…”
Section: Head and Neck Cancersmentioning
confidence: 56%
“…Chitapanarux et al [12] compared carboplatin with cisplatin in a prospective randomized trial, finding no difference in the 3-year DFS (p = 0.9613) and OS (p = 0.9884). However, some retrospective analyses found that concurrent carboplatin was a negative prognostic factor for HNSCC and NPC [24,25,26]. Zhang et al [11] reported the use of oxaliplatin for CCRT.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of concurrent chemotherapy to radiotherapy (RT) for LAHNSCC results in an absolute survival benefit of 6.5% at 5-years, with greater benefit with platinum-based chemotherapy [1]. Among the concurrent platinum agents, single-agent cisplatin is superior to single-agent carboplatin and equivalent to carbo-platin with 5-fluorouracil (5FU) in retrospective analyses [2,3]. …”
Section: Introductionmentioning
confidence: 99%